Innate mechanism or acquired instrument: nature of language as basis for understanding cognitive abilities of human beings - O. V. Gorodovich (Омский научный вестник: Серия "Общество. История. Современность")
The article contains a critical review of modern problems of Universal Grammar theory by Noam Chomsky. It examines the origins of the theory, the process of its development, the transition to the ‘Second Cognitive Revolution’ and some recent objections to Chomsky’s hypothesis about the innate status of our knowledge of language.